A complex chromosomal rearrangement detected prenatally and studied by fluorescence in situ hybridization - Batista, Denise A.S.; Tuck-Muller, Cathy M.; Martinez, Jose E.; Kearns, William G.; Pearson, Peter L.; Stetten, Gail (Springer Nature, 1993)
We report of case of a complex chromosomal rearrangement detected prenatally and studied with traditional banding methods and fluorescence in situ hybridization. The combination of these techniques showed that four chromosomes were involved in the translocation. Nine breakpoints were proposed to explain these results. Some of the findings could only be detected with fluorescence in situ hybridization, demonstrating the usefulness of this technique in characterizing chromosomal abnormalities that would otherwise be difficult to interpret correctly with classical cytogenetics alone. © 1993 Springer-Verlag.